Does Prenatal Valproate Interact with a Genetic Reduction in the Serotonin Transporter? A Rat Study on Anxiety and Cognition - Ellenbroek, Bart A.; August, Caren; Youn, Jiun (Frontiers in Neuroscience, 2016)
There is ample evidence that prenatal exposure to valproate (or valproic acid, VPA) enhances the risk of developing Autism Spectrum Disorders (ASD). In line with this, a single injection of VPA induces a multitude of ASD-like symptoms in animals such as rats and mice. However, there is equally strong evidence that genetic factors contribute significantly to the risk of ASD and indeed, like most other psychiatric disorders, ASD is now generally thought to results from an interaction between genetic and environmental factors. Given that VPA significantly impacts on the serotonergic system, and serotonin has strong biochemical and genetic links to ASD, we aimed to investigate the interaction between genetic reduction in the serotonin transporter and prenatal valproate administration. More specifically, we exposed both wildtype (SERT+/+) rats and rats heterozygous for the serotonin transporter deletion (SERT+/-) to a single injection of 400 mg/kg VPA at gestational day (GD) 12. The offspring, in adulthood, was assessed in four different tests: Elevated Plus Maze and Novelty Suppressed Feeding as measures for anxiety and prepulse inhibition (PPI) and latent inhibition as measures for cognition and information processing. The results show that prenatal VPA significantly increased anxiety in both paradigm, reduced PPI and reduced conditioning in the latent inhibition paradigm. However, we failed to find a significant gene – environment interaction. We propose that this may be related to the timing of the VPA injection and suggest that whereas GD12 might be optimal for affecting normal rat, rats with a genetically compromised serotonergic system may be more sensitive to VPA at earlier time points during gestation. Overall our data are the first to investigate gene * environmental interactions in a genetic rat model for ASD suggest that timing may be of crucial importance to the long-term outcome.